2013
DOI: 10.5535/arm.2013.37.5.633
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Swallowing Functions Between Brain Tumor and Stroke Patients

Abstract: ObjectiveTo compare the swallowing functions according to the lesion locations between brain tumor and stroke patients.MethodsForty brain tumor patients and the same number of age-, lesion-, and functional status-matching stroke patients were enrolled in this study. Before beginning the swallowing therapy, swallowing function was evaluated in all subjects by videofluoroscopic swallowing study. Brain lesions were classified as either supratentorial or in-fratentorial. We evaluated the following: the American Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
(20 reference statements)
1
10
1
1
Order By: Relevance
“…Fourth, there was a relatively smaller sample size in the second group when compared with the first group. Post-stroke dysphagic patterns show differences according to location of the brain lesion, whether it was a supratentorial or infratentorial lesion [ 6 16 ], unlike our study which showed no differences between supratentorial or infratentorial lesions. This may have been due to the discrepancy in the sample size between the two groups.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Fourth, there was a relatively smaller sample size in the second group when compared with the first group. Post-stroke dysphagic patterns show differences according to location of the brain lesion, whether it was a supratentorial or infratentorial lesion [ 6 16 ], unlike our study which showed no differences between supratentorial or infratentorial lesions. This may have been due to the discrepancy in the sample size between the two groups.…”
Section: Discussioncontrasting
confidence: 81%
“…Dysphagia is a disorder of deglutition that affects oral, pharyngeal, and esophageal phases of swallowing [ 5 ]. Interruption of voluntary control of mastication, bolus transport, and impairment of facial, lip, or tongue motor control are caused by cerebral, cerebellar, or brain stem strokes [ 6 ] and can result in impairment of swallowing physiology [ 7 ]. Dysphagia should be treated, as it can lead to health-related complications, such as pneumonia as well as nutrition and hydration deficits [ 7 8 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of these events can be decreased through rehabilitation specific to swallowing, as functional dysphagia improvements have been reported [13]. Patients with infratentorial tumors have dysphagia at higher frequencies than those with supratentorial lesions and no difference in frequency was noted between malignant and benign tumors [34].…”
Section: Dysphagiamentioning
confidence: 99%
“…Do czynników ryzyka zachłystowego zapalenia płuc należą wszystkie stany prowadzące do zaburzeń świadomości -w sposób odwrotnie proporcjonalny do punktacji uzyskanej przez chorego w skali Glasgow [18] -w tym stosowanie farmakologicznej sedacji [4], szczególnie w połączeniu z długotrwałym przebywaniem w pozycji leżącej na plecach [19]. Zachłystowe zapalenie płuc występuje częściej u pacjentów po udarze lub urazie mózgu [4,14], u chorych na nowotwory regionu głowy i szyi [20][21][22], u pacjentów z wewnątrzczaszkowym efektem masy [23]. Kolejnymi czynnikami ryzyka są: zniesiony odruch kaszlu [4,21], obecność masy patologicznej w drogach oddechowych [21] oraz przewlekłe choroby płuc upośledzające oczyszczanie dróg oddechowych [4,14], takie jak POChP.…”
Section: Czynniki Ryzyka I Epidemiologia Zapaleń Płucunclassified